Structure of the C-terminal domain of Tup1, a corepressor of transcription in yeast - Sprague, Elizabeth R. (Oxford University Press, 2000)
The Tup1–Ssn6 corepressor complex regulates the expression of several sets of genes, including genes that specify mating type in the yeast Saccharomyces cerevisiae. Repression of mating-type genes occurs when Tup1–Ssn6 is brought to the DNA by the Matα2 DNA-binding protein and assembled upstream of a- and haploid-specific genes. We have determined the 2.3 Å X-ray crystal structure of the C-terminal domain of Tup1 (accesion No. 1ERJ), a 43 kDa fragment that contains seven copies of the WD40 sequence motif and binds to the Matα2 protein. Moreover, this portion of the protein can partially substitute for full-length Tup1 in bringing about transcriptional repression. The structure reveals a seven-bladed β propeller with an N-terminal subdomain that is anchored to the side of the propeller and extends the β sheet of one of the blades. Point mutations in Tup1 that specifically affect the Tup1–Matα2 interaction cluster on one surface of the propeller. We identified regions of Tup1 that are conserved among the fungal Tup1 homologs and may be important in protein–protein interactions with additional components of the Tup1-mediated repression pathways.